LLMs as Clinical Instruments—Toward Verifiable Reasoning - Martin P. Paulus; John Torous (JAMA Psychiatry, 2026)
This Viewpoint discusses considerations in training mental health clinicians and implementing institutional workflows to use large language models (LLMs) as clinical instruments for improving care.